BERMUDA GRASS FOLIAR CHLOROPHYLL CONTENT INFLUENCED BY LUMINOSITY AND SUBSTRATE (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The objective of this work was to evaluate the influence of luminosity and different substrates on Bermuda grass (Cynodon dactylon x C. transvaalensis) chlorophyll a and b contents and root system evaluation. The experiment was conducted in a 5 x 4 factorial scheme (substrates x luminosities), in completely randomized design with 20 treatments and 3 replicates. The substrates were: S1 = Soil, S2 = Soil + sand (2:1), S3 = Soil + organic matter (1:1), S4 = Soil + organic matter + sand (2:1:1) and S5 = organic matter + sand (3:1), in four luminosity conditions: full sun, 30%, 50% and 80% of shading for six months. We evaluated chlorophyll a and b. After 180 days after planting, bigger contents of both chlorophyll were found according to increment of shading.